An in-house Composix™-based pubovaginal sling trial for female stress urinary incontinence: Five-year comparative followup to tension-free and transobturator vaginal tapes - Ben-Zvi, Tal; Moore, Katherine; Haidar, Nadim; Gregoire, Mireille (Canadian Urological Association Journal, 2017)
Introduction: We compared the efficacy of three slings in the long-term treatment of stress urinary incontinence (SUI): tension-free vaginal tape (TVT), vaginal tape-obturator (TVT-O), and an in-house two-layered polypropylene mesh with a submicronic polytetrafluoroethylene (Composix™). Our primary endpoint was the objective measurement of continence (24-hour pad test). Secondarily, we measured the satisfaction and complication rates. Methods: This prospective, non-randomized study included 128 patients with SUI. Preoperative evaluation included medical history, physical exam, 24-hour pad test, Urinary Incontinence Quality of Life Scale (IQOL), FPSUND, and global satisfaction questionnaires. Patients were followed at one month postoperative, biannually for two years, and then annually for a total of five years. Followup visits included a focused questionnaire, physical exam, satisfaction questionnaire, 24-hour pad test, IQOL, and FPSUND questionnaires. Results: Composix, TVT, and TVT-O groups included 60, 34, and 34 patients, respectively. No significant differences were found in baseline characteristics except for the pad test. Length of catheterization was the only immediate operative significant parameter (Composix 4.7 days vs. TVT 1.1 days vs. TVT-O 2.6 days; p=0.03). The entire cohort had significant improvements in their IQOL, FPSUND, and pad test at one and four years (p<0.01). The cohortwide 24-hour pad test average weight was 30.4 g preoperatively vs. 5 g at 12 months (p<0.00001) (Composix 37 to 5 g, TVT 83 to 4 g, and TVT-O 55 to 5 g). The Composix group had a higher number of minor complications (Clavien I, II) and secondary procedures. Conclusions: This single-surgeon cohort with five-year followup demonstrated a large improvement and maintenance of continence in all three surgical groups. The Composix-based sling provided comparable continence outcomes at a fraction of the cost; however, its increased morbidity and higher complication rate raise concerns over future use